Impact Dynamic Behavior and Deformation Mode of a Lightweight-Coated Honeycomb Steel Structure - Luo, Ning; Yuan, Yishuo; Fan, Xueru; Suo, Yunchen; Mou, Gongyu (Frontiers in Materials, 2022)
Honeycomb materials have attracted people's attention because of their light weight, high specific strength, high specific stiffness and excellent impact resistance and energy absorption. At present, they have been widely used in aerospace, transportation, mechanical construction, energy and chemical industry. The mechanical properties of honeycomb steel with special coating under quasi-static and dynamic compression were studied by the universal strength testing machine (TAWD-2000) and split Hopkinson pressure bar devices (SHPB). The results showed that the stress-strain curves obtained from quasi-static compression experimental showed the characteristics of three typical deformation stages of porous materials: elastic deformation stage; stress platform stage; densification stage. Due to the loading time of dynamic compression experiment is very short and the effect of sample height, there was no densification stage in the stress-strain curves. The compression deformation process of the samples was captured by the high-speed photography equipment, and its different deformation and failure modes were analyzed in combination with the characteristics of stress-strain curves. The increasing relationship between peak stress and strain rate showed that the honeycomb structure has strong strain rate sensitivity. The dynamic energy absorption characteristics of honeycomb materials were described and analyzed by using dynamic energy absorption capacity and dynamic energy absorption efficiency. By using finite element simulation software, the same structure of the honeycomb steel was modeled and analyzed to explore the causes of dynamic compression failure.